The big black book : become who you are-there are no guarantees - Tharcher, Nicholas; Willis, Jack; Matheny, Joseph; Black, S. Jason; Jensen, Crag; Iwema, Calvin (Connecticut Bottom line book, 2003)
"When Dr. Hyatt first proposed The Black Books, circa 2002 , it seemed a brilliant idea. He has always been an "elitist"-though it amazed him that many readers of his books cannot seem to get that simple fact through their heads-and this would be a great opportunity to publish more of his most radical ideas. If you are a "Mutant"-as Dr. Hyatt refers to that small percentage of humanoids who appear to have a working brain-hopefully you've figured out the nature and purpose of The Big Black Book. On the other hand, if you're a Mute or an Anti-Mutant-as are the vast majority of the humanoids on this wretched planet-what the hell are you doing here? You're wasting your time-and ours"--